Autopercepção e condições de saúde bucal em gestantes - Jeremias, Fabiano [UNESP]; Silva, Silvio Rocha Corrêa da [UNESP]; Valsecki Jr, Aylton [UNESP]; Tagliaferro, Elaine Pereira da Silva [UNESP]; Rosell, Fernanda Lopez [UNESP] (My University, 2010)
This study ev aluated oral health indic ators by determining the pr evalence of dental c aries, periodontal diseases, prosthetic conditions and need in pr egnant women; identifi ed self-perceived oral health status and evaluated association bet ween variables. A clinical examination was performed in fi fty pregnant women assisted in the Preventive Dentistry Clinic-FOAr-UNESP using traditional oral health indicators: DMFT, C ommunity Periodontal Index ( CPI) and pr osthetic c onditions. A semi-struc tured questionnair e was applied to identify oral health perception and to collect sociodemographic variables. For data analysis, pregnant women were allocated in three groups according to their oral health perception (good, fair, poor) and compared according to clinical variables by the Kruskal-Wallis and Dunn tests. DMFT was high, all of them showed periodontal changes, most do not use and do not r equire any type of prosthesis; 36% considered their oral appearance as good. There was signifi cant diff erence between groups for the DMFT index and prosthetic need. It may be concluded that despite dental caries experience of pregnant women was found to be high, the prosthetic need have been detected in most of them and the presence of calculus was observed in all the volunteers, the majority considered their oral health status satisfactory.

O estudo avaliou indicadores de saúde bucal em gestantes por meio da determinação da prevalência de cárie dentária, periodont opatias, uso e necessidade de próteses; identifi cou a autopercepção de condições de saúde bucal e avaliou a associação entre as variávies. Exame clínico foi realizado em 50 gestantes atendidas na Clínica de Odont ologia Preventiva e Sanitária da FO Ar-UNESP utilizando indicadores tradicionais de saúde: IPC, CPO-D e avaliação protética. Um questionário semi-estruturado foi aplicado para identifi car a per cepção sobre a saúde bucal e c oletar variáveis sóciodemográfi cas. Para análise, três grupos foram formados segundo a percepção de saúde bucal: boa, regular, ruim, e comparados segundo as variáveis clínicas, pelos testes Kruskal-Wallis e Dunn. O CPO-D das gestantes foi considerado alto; todas apresentaram alterações periodontais; a maioria não utilizava e não necessitava de nenhum tipo de prótese; 36% das gestantes consideraram boa sua aparência bucal. Houve diferença signifi cativa entre os grupos para o índice CPOD e para nec essidade de pr ótese. Embora a experiência de cárie t enha sido alta, a nec essidade de pr ótese ter sido det ectada na maior par te da amostra e a pr esença de cálculo dental t enha sido obser vada em todas as voluntárias, a maioria considerou sua condição bucal satisfatória.
Self-perception and oral health status in pregnant women
Keywords: Self-perception; Oral health; Pregnant women; Autopercepção; Saúde bucal; Gestantes.